The Influence of Educational Sector and Government Spending on Healthcare, Household Consumption for Food and Poverty Levels on Human Development Index in Indonesia - Eva Novita Mirna Lubis (Proceedings of AICS - Social Sciences, 2017)
The purpose of these papers is to find out if government spending sectors of education and health sectors, household consumption for food and poverty levels against the human development index in Indonesia. The type of data used in this research is time series data from 2009 until 2013 obtained from the Central Bureau of Statistics Indonesia. Hypothesis testing of the value of F-count is 426.419 with a significant level of 0.002. While F table at 95% confidence level (α = 0.05) is 19.25. Since both calculations are F-count F- table and its significance level 0.002 0.05 indicates that the independent variables are Government Education Expenditure (X1), Government Health Expenditure (X2), Household Consumption for Food (X3), and Poverty Rate (X4) , simultaneously is a significant influence on the dependent variable that is HDI (Y) year 2010-2016.The results of this research is government spending on healthcare and education sectors, household consumption for food and poverty levels have an effect on the human development index in Indonesia.